Curriculum theory : conflicting visions and enduring concerns - Schiro, Michael 1942- (Sage, 2013)
The Second Edition of Curriculum Theory: Conflicting Visions and Enduring Concerns presents a clear, unbiased, and rigorous description of the major curriculum philosophies that have influenced educators and schooling over the last century. Author Michael Stephen Schiro analyzes four educational visions--Scholar Academic, Social Efficiency, Learner Centered, and Social Reconstruction--to enable readers to reflect on their own educational beliefs and more productively interact with educators who might hold different beliefs. New to this edition: In chapter 2, the section on teaching has been reorganized and a new subsection added on teachers as transmitters, mediators, or translators; several new sections on the learner centered ideology, including one major section that provides a description and analysis of a learner centered curriculum. Other sections include elements such as a discussion of the relationship between knowledge and experience, and the nature and structure of the learning environment of the ideology; seven new sections have been added to chapter 6, including six plays in which four teachers discuss their beliefs about enduring curricular issues and related current "hot" curriculum topics in ways that highlight the differences between the ideologies; and an additional section in chapter 6 discusses in how each of the ideologies takes advantage of the use of technology in curriculum and during instruction.